From feedback to follow-up in the third turn of IRF sequences: A challenge to promote genuine interaction in EFL classes - Pinzón Jácome, Laura Margarita; Lozano Jaimes, Carlos Augusto; Dueñas Angulo, Laura Cristina (Rastros Rostros, 2016)
Introduction: In this paper, we present an analysis of the teacher-student interaction patterns in efl classes found at a Colombian private university.Methodology: This analysis was made during a qualitative case study in which 36 class observations were conducted. Data were coded and further categorized with the help of Nvivo10 software.Findings: Teacher-student interaction was the most common type of classroom exchange. A three-turn sequence, commonly referred to as irf, was chief among those interactions. In an irf exchange the teacher (I)nitiates the interaction, the student (R)esponds and the teacher provides (F)eedback. The third turn in irf exchanges was scarcely used to follow-up on students’ responses. Furthermore, we present the implications of using the third turn for both feedback and follow-up.Conclusions: Given the analysis made, the authors conclude that teachers should use the third turn for follow-up if the goal is to promote genuine linguistic interaction and engage students in meaningful communication.
Keywords: feedback; follow-up; interaction; irf